Pediatric autoimmune encephalitis associated with anti-glutamic acid decarboxylase 65 antibody two cases report and literature review - Ren, C H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2021)
Objective: To investigate the clinical features and prognosis of pediatric autoimmune encephalitis associated with anti-glutamic acid decarboxylase 65 (GAD65) antibody. Methods: Clinical data of 2 patients diagnosed as autoimmune encephalitis associated with anti-GAD65 antibody at Department of Neurology, Beijing Children's Hospital in 2019 were analyzed retrospectively. A literature search with "anti-GAD65 antibody""encephalitis""epilepsy" or "cerebellar ataxia" as key words was conducted at China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform and PubMed (up to January 2020). The clinical features and prognosis of pediatric cases with complete clinical data were retrieved and summarized. Results: Two patients with positive anti-GAD65 antibody of serum and cerebrospinal fluid were both females. The onset age of case 1 was 57 months and her main clinical manifestations were fever and unconsciousness. The cranial magnetic resonance imaging (MRI) showed diffuse T2 weighted imaging (T2WI) abnormal signals, and the electroencephalogram (EEG) showed slow waves. The onset age of case 2 was 80 months and her main clinical manifestations of were recurrent focal seizures, memory loss, and headache. The MRI showed high T2WI signal in bilateral hippocampus, and the EEG showed abnormal discharge involving the temporal area. Both cases were treated with methylprednisolone and intravenous immunoglobulin, the short-term symptoms of them were both improved. They were followed up for 6 months and 1 year respectively, the case 1 recovered completely, and the case 2 still had focal seizures. Six English reports which included 6 cases were retrieved. Together with these 2 cases, a total of 8 cases were analyzed. The clinical symptoms included seizures (6 cases), memory loss (4 cases), loss of consciousness (3 cases), behavioral abnormalities (3 cases), cognitive impairment (2 cases), headache (2 cases), autonomic symptoms (1 case), ataxia (1 case), dysphagia (1 case), and aphasia (1 case). There were 5 cases with cranial MRI abnormalities in the acute phase or sub-acute phase, of whom 3 cases had the limbic system involvement, and 2 cases were mainly had extra limbic area involvement. Three cases had hippocampal atrophy or sclerosis during follow-up. All 8 patients were treated with immunotherapy. After immunotherapy, all patients had short-term improvement. Follow-up for 6 months to 6 years showed that 3 cases with extra limbic encephalitis improved to baseline levels, and 5 limbic encephalitis cases had poor outcomes, including 1 death and 4 cases still had focal epilepsy. Conclusions: Pediatric anti-GAD65 antibody associated autoimmune encephalitis is a rare but treatable disease, including limbic encephalitis and extra limbic encephalitis. The most common clinical manifestations are seizures and memory impairment. Early diagnosis and immunotherapy can improve the symptoms in a short time. But patients with limbic encephalitis often had refractory epilepsy in the chronic phase, and have a poor long-term outcome